Carotid artery stenting: Current state of evidence and future directions. (6th February 2019) - Lamanna, Anthony; Maingard, Julian; Barras, Christen D.; Kok, Hong Kuan; Handelman, Guy; Chandra, Ronil V.; Thijs, Vincent; Brooks, Duncan Mark; Asadi, Hamed
Abstract : Both carotid endarterectomy (CEA) and carotid artery stenting (CAS) are common treatments for carotid artery stenosis. Several randomized controlled trials (RCTs) have compared CEA to CAS in the treatment of carotid artery stenosis. These studies have suggested that CAS is more strongly associated with periprocedural stroke; however, CEA is more strongly associated with myocardial infarction. Published long‐term outcomes report that CAS and CEA are similar. A reduction in complications associated with CAS has also been demonstrated over time. The symptomatic status of the patient and history of previous CEA or cervical radiotherapy are significant factors when deciding between CEA or CAS. Numerous carotid artery stents are available, varying in material, shape and design but with minimal evidence comparing stent types. The role of cerebral protection devices is unclear. Dual antiplatelet therapy is typically prescribed to prevent in‐stent thrombosis, and however, evidence comparing periprocedural and postprocedural antiplatelet therapy is scarce, resulting in inconsistent guidelines. Several RCTs are underway that will aim to clarify some of these uncertainties. In this review, we summarize the development of varying techniques of CAS and studies comparing CAS to CEA as treatment options for carotid artery stenosis.